2015
DOI: 10.1039/c5sm00508f
|View full text |Cite
|
Sign up to set email alerts
|

An injectable and fast-degradable poly(ethylene glycol) hydrogel fabricated via bioorthogonal strain-promoted azide–alkyne cycloaddition click chemistry

Abstract: Biocompatible and degradable injectable materials prepared via bioorthogonal reactions are highly promising for biomedical applications because they can be formed in situ and administered in a minimally invasive way. In this work, a PEG-based injectable hydrogel was fabricated via a copper-free, strain-promoted azide-alkyne cycloaddition (SPAAC) click chemistry. Azide and cyclooctyne moieties on the PEG backbones underwent a rapid click reaction to trigger the formation of the hydrogel within several minutes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Strain-promoted azide-alkyne cycloaddition (SPAAC) click chemistry has drawn increasing attention recently due to the mild reaction conditions and bioorthogonality (Xu et al, 2014 ). An injectable and degradable PEG-based hydrogel has been prepared via the bioorthogonal SPAAC click chemistry (Jiang et al, 2015 ). Michael addition reaction is the nucleophilic addition of a carbanion or a nucleophile to an α, β-unsaturated carbonyl compound.…”
Section: Materials and Crosslinking Methods For Functional Hydrogels mentioning
confidence: 99%
“…Strain-promoted azide-alkyne cycloaddition (SPAAC) click chemistry has drawn increasing attention recently due to the mild reaction conditions and bioorthogonality (Xu et al, 2014 ). An injectable and degradable PEG-based hydrogel has been prepared via the bioorthogonal SPAAC click chemistry (Jiang et al, 2015 ). Michael addition reaction is the nucleophilic addition of a carbanion or a nucleophile to an α, β-unsaturated carbonyl compound.…”
Section: Materials and Crosslinking Methods For Functional Hydrogels mentioning
confidence: 99%
“…Jiang et al reported a fast degrading, injectable hydrogel system made from alkynemodified PEG and azide-modified PEG cross-linked via SP-AAC reaction. Their results showed excellent properties including in situ gel formation ability under in vivo conditions with mild immunogenic response [70]. Liu et al revealed poly(e-caprolactone)-based hyper-branched dendrimers which were cross-linked via SP-AAC reaction exhibiting high mechanical properties and biocompatibility.…”
Section: Strain-promoted Azide-alkyne Cycloaddition (Sp-aac)-based CLmentioning
confidence: 99%
“…12). SPAAC has been successfully applied to the preparation of injectable hydrogels [60] and cellencapsulating hydrogels. DeForest and Anseth have worked extensively on SPAAC crosslinking.…”
Section: Azide-alkyne Cycloadditionmentioning
confidence: 99%